Program održivog razvoja Svete Nedelje, Jastrebarskog i Samobora (University of Maribor Press, 2024)
The Sustainable Development Program of Sveta Nedelja, Jastrebarsko and Samobor. The surroundings of Zagreb are known as an area with abundant natural beauty, a pleasant rhythm of life, preserved heritage, and a rich offering of local cuisine. The area served as a place of education for tourism, marketing and rural development students from 9 universities in Croatia, Slovenia, Serbia, Montenegro and the Netherlands. Through guided tours of various locations in Sveta Nedelja, Jastrebarsko and Samobor, the students learned about the tourist offer to recognize the potential for further tourism development. Under the guidance of the hosts and their mentors, with an aim to improve the business and optimize the current tourism offer, the students came up with innovative and creative solutions that form the main content of this monograph. The scientific monograph "The Sustainable Development Program of Sveta Nedelja, Jastrebarsko and Samobor" is the result of local stakeholders’ initiatives to promote the strategic development of tourism in Central Croatia and Zagreb County.